Utilization of the VivaVideo Application During Covid-19 - Qian, Shodiq; Thomas, Defoort; Samir, Katayama; Jie, Lie (Journal International Inspire Education Technology, 2023)
The use of the VivaVideo application for education during the Covid-19 pandemic is very much needed because distance learning is carried out; the VivaVideo application makes it easy for educators to carry out a fun learning process and does not require an internet network. In remote areas with limited internet, using the VivaVideo application as a learning medium is a suitable solution because VivaVideo does not need an internet network; educators can use the VivaVideo application as a learning medium by sharing videos explaining material made in the VivaVideo application to students. An example is the use of the VivaVideo application in elementary schools as a social science learning medium.